A framework for increasing business value from social media. Issue 1 (1st January 2018) - Trkman, Marina; Trkman, Peter
Abstract: Organisations are investing heavily in various social media applications. Several case studies show that such undertakings may be promising at first glance, but often amount to little. More attention has to be paid to the factors that influence the business value of a social media application. The paper proposes a framework which argues that the business value of a social media activity depends on having a correctly identified purpose of its implementation (scope and targeted benefits), on the technological solution and also on user involvement (user groups, users' motivation and skills). The framework is evaluated with a longitudinal case study of a wiki in a software development company where an assessment of the business value of the wiki at two different points in time was made. The case study shows how the interplay of components led to failure at one time point and success at the other.